2005
DOI: 10.1359/jbmr.2005.20.6.1065
|View full text |Cite
|
Sign up to set email alerts
|

An Uncoupling Agent Containing Strontium Prevents Bone Loss by Depressing Bone Resorption and Maintaining Bone Formation in Estrogen-Deficient Rats

Abstract: Trabecular bone loss in estrogen deficiency is associated with enhanced bone resorption with a smaller increase in bone formation. We previously reported that low doses of strontium can increase trabecular bone volume in rodents by affecting bone resorption and formation. In this study we determined the effect of a new divalent strontium salt (S12911) on bone loss induced by E2 deficiency. Sprague-Dawley female rats (230 g, n = 15-25 per group) were sham operated or ovariectomized (OVX) and treated with 170-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
1
17

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(148 citation statements)
references
References 30 publications
8
122
1
17
Order By: Relevance
“…4 In animals, Sr prevents bone loss in OVX rats 7,8 and increases bone mass in intact rats 16 and monkeys. 17 However, information of the anabolic effect of Sr on trabecular bone is limited, especially at the structural and tissue level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In animals, Sr prevents bone loss in OVX rats 7,8 and increases bone mass in intact rats 16 and monkeys. 17 However, information of the anabolic effect of Sr on trabecular bone is limited, especially at the structural and tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…4 In OVX rats, SR treatment prevented bone loss by increasing the bone formation maker and decreasing the bone resorption marker. 7,8 The cellular and molecular mechanism of the anabolic effect of strontium (Sr) on bone remains poorly understood. In vitro studies suggest that Sr can promote osteoblast proliferation and differentiation.…”
mentioning
confidence: 99%
“…Studies in rats have demonstrated that in addition to the increase in bone mass, there is an increase in cortical thickness and an improvement in trabecular and cortical microarchitecture, leading to an increased bone quality and strength [Ammann et al 2004[Ammann et al , 2007. In ovariectomized rats, an established animal model for postmenopausal osteoporosis, strontium ranelate was able to prevent bone loss by decreasing bone resorption while maintaining bone formation not only in the short term [Marie et al 1993], but also in the long term [Bain et al 2009]. In this latter study, the ovariectomy-induced decline in bone mass, volume and strength was prevented by achieving a plasma concentration of strontium ranelate similar to that obtained in women with osteoporosis treated with the therapeutic daily dose of 2 g.…”
Section: Determinants At the Tissue Level: In Vivo Evidencementioning
confidence: 99%
“…Strontium ranelate acts on both bone formation indices and bone resorption indicators. Indeed, strontium ranelate prevents trabecular bone loss, decreases bone resorption and increases or maintains bone formation in the ovariectomised rat model or in rats subjected to hindlimb immobilisation [133,134]. Strontium ranelate also reduces bone resorption and enhances bone mass and strength in mice, rats and monkeys [135][136][137].…”
Section: Drugs/agents That Target Bone Remodellingmentioning
confidence: 99%